2004
DOI: 10.4081/monaldi.2004.688
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial low-grade MALT lymphoma causing unilateral hypertranslucency

Abstract: Mucosa-associated lymphoid tissue-derived lymphoma (MALT lymphoma) arises not only from the stomach but also from various non-gastrointestinal sites. A thirty two year old woman, suffering from breathlessness for one year, had been treated for bronchial asthma. A chest radiograph showed a mediastinum and heart transposition to the right side and emphysema of the left lung. In the thorax spiral tomography, a mass narrowing left main bronchi, five centimeters in length from the carina, was seen. A fiberoptic bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…From the time when there were no findings at all, we were able to follow up the course of the disease over a period of 4 years. The change in size of EML appeared to be variable from a report where the tumour size did not change over 16 years 34 to another case that caused significant stenosis of the left mainstem bronchus 10 . As for our case, the tumour size increased during subsequent annual follow ups that indicated a need for aggressive treatment measure.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…From the time when there were no findings at all, we were able to follow up the course of the disease over a period of 4 years. The change in size of EML appeared to be variable from a report where the tumour size did not change over 16 years 34 to another case that caused significant stenosis of the left mainstem bronchus 10 . As for our case, the tumour size increased during subsequent annual follow ups that indicated a need for aggressive treatment measure.…”
Section: Discussionsupporting
confidence: 42%
“…We herein report a case of EML that was diagnosed through a chest computed tomography (CT) during an annual health checkup which was successfully treated with radiotherapy. To the best of our knowledge, only 48 cases of EML have been reported in the literature 1–38 . To date, a comprehensive review of this rare condition is not available.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports on endobronchial BALT lymphoma in the lobar bronchus with lobar atelectasis and left main bronchus with unilateral hyperlucent left lung, but most of these are the case report findings of a single patient (6, 18, 19). …”
Section: Discussionmentioning
confidence: 99%
“…According to Erbaycu et al (19) endobronchial BALT lymphomas can affect both genders equally. There are other previous case reports which have shown female predominancy (18, 20).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that endobronchial MALT lymphoma was seen in only 1 (1.3%) of 75 cases of nongastrointestinal MALT lymphoma [5]. Including the present case, 28 cases [[6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]] in a PubMed search and 7 cases in Japanese journals of primary endobrochial MALT lymphoma have been reported.…”
Section: Discussionmentioning
confidence: 49%